Listening to the Experiences and Concerns of Pre-Service Teachers During Teaching Practice Programme - Darshana Sharma (MIER Journal of Educational Studies Trends and Practices, 2015)
Teaching Practice is widely recognised as the sine-qua-non of any teacher education programme. It is a component in the teacher preparation programme where prospective teachers are provided with an opportunity to put their theoretical studies into practice, get feedback, reflect on practice and consequently further improve their teaching skills. As teaching practice is an important component of a teacher education programme, considerable attention must be given to make it more effective and fruitful. This paper is based on a research study conducted to know pre-service teachers’ experiences of the quality of teaching practice and the common concerns they have during teaching practice. On the basis of focussed group discussion a total of five themes were identified, these are (1) usefulness of teaching practice (2) experiences/concerns with pupils’ behaviour (3) experiences/concerns with own behaviour (4) experiences/concerns with supervisors’ behaviour (5) experiences/concerns with institutional and personal adjustments. The outcome of the focussed group discussion was used to prepare a structured questionnaire. Among other things, the study recommended rigorous practical training in lesson planning, demonstration lessons by teacher educators, simulated teaching before the commencement of practice teaching, school orientation programmes, a separate internship of two weeks and writing a journal by student teachers during teaching practice.